Analisis Pengaruh Profitabilitas, Transfer Pricing, dan Green Accounting terhadap Tax Avoidance - Ribka Septiani Natty; Ismail Marthinus; Grace Orlyn Sitompul (Journal of Innovative and Creativity, 2025)
This study examines the influence of Profitability, Transfer Pricing, and Green Accounting on Tax Avoidance in oil, gas, and coal subsector companies listed on the Indonesia Stock Exchange during 2022–2024. Using a quantitative approach with multiple linear regression, the study analyzes secondary data from audited financial reports. The results show that Profitability and Transfer Pricing significantly and positively affect Tax Avoidance, indicating that firms with higher profits and related-party transactions tend to minimize taxes within legal boundaries. Meanwhile, Green Accounting has no significant effect, suggesting that sustainability disclosures have not yet influenced taxation behavior in this sector. The coefficient of determination indicates that the three variables explain 21.5% of Tax Avoidance, implying that other factors such as leverage, company size, corporate governance, and capital intensity may also play roles. The novelty of this research lies in integrating Green Accounting into the context of Indonesia’s extractive industries. The study concludes that financial and transactional aspects remain the main drivers of Tax Avoidance, while environmental factors are still underrepresented.